Communicating paradigmatic intellectual orientations: the mediating role of persistent theme - Strauss, D. F. M. (Department of Communication Science, University of the Free State, 2015)
All humans have the capacity to live in organised societies and to communicate the basic patterns of such societies to forthcoming generations. If they are accompanied by persistent themes operative within intellectual traditions and passed on to subsequent intellectual trends, then the ongoing power of paradigmatic orientations is demonstrated. This article focuses on the historically mediated communication of two opposing but powerful paradigmatic views on the relation between human beings and human society. Atomistic or individualistic approaches will be contrasted with holistic or universalistic views. The historical connection will be traced as persistent themes present in the paradigmatic stance of Greek thinkers (such as Callicles, Protagoras, Plato and Aristotle), medieval intellectuals (Augustine and Thomas Aquinas), transitional figures (William of Ockham, Jean of Jandun and Marsilius of Padua), modern thinkers (Hobbes, Locke and Kant), the switch from Enlightenment rationalism and individualism to the irrationalistic individualism of early Romanticism, and the full-blown Romantic emphasis on an irrationalistic universalism (the transpersonal national spirit of each people, Volk – Von Schlegel, Herder, Hegel and Fichte). After considering the subsequent communication of some relevant turns during the 19th and 20th century, it will be briefly pointed out that human nature does not determine societal structures, just as little as one or another societal entity (the Volk, state or church) embraces individuals or the other societal collectivities and communities fully as integral parts. When persistent paradigmatic themes are communicated to later scholars (Holton) amidst changing historical contexts, the directing power of diverging basic motives and the inevitability of communicative historical continuity is amply demonstrated.
Keywords: Atomism/individualism; Holism/universalism; Nominalism; Form-matter motive; Nature-grace motive; Nature-freedom motive; Rationalism; Irrationalism